2017
DOI: 10.1007/s00442-017-3962-9
|View full text |Cite
|
Sign up to set email alerts
|

Root chemistry and soil fauna, but not soil abiotic conditions explain the effects of plant diversity on root decomposition

Abstract: Plant diversity influences many ecosystem functions including root decomposition. However, due to the presence of multiple pathways via which plant diversity may affect root decomposition, our mechanistic understanding of their relationships is limited. In a grassland biodiversity experiment, we simultaneously assessed the effects of three pathways-root litter quality, soil biota, and soil abiotic conditions-on the relationships between plant diversity (in terms of species richness and the presence/absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 108 publications
2
15
0
1
Order By: Relevance
“…In contrast to the increasing aboveground litter decomposition, our results also support the finding that a decrease in root N content with increasing richness may slow the root decomposition (Chen et al. , b). This can be interpreted by the fact that although the increasing plant richness decreases the initial N and lignin contents of root, the effect of N content change on root decomposition is the higher than the lignin contents, which leads the net effect of increasing plant richness on the root decomposition and N release is negative.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast to the increasing aboveground litter decomposition, our results also support the finding that a decrease in root N content with increasing richness may slow the root decomposition (Chen et al. , b). This can be interpreted by the fact that although the increasing plant richness decreases the initial N and lignin contents of root, the effect of N content change on root decomposition is the higher than the lignin contents, which leads the net effect of increasing plant richness on the root decomposition and N release is negative.…”
Section: Discussionsupporting
confidence: 90%
“…Single species plots had the higher tissue N and lignin contents both above‐ and belowground, which supports the finding that the tissue N content decreases with increasing species richness (Chen et al. , b). Plot level tissue quality changes were mainly dependent on the species tissue quality in pant community.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…After determining lignin and N concentrations, we estimated the lignin/N ratio. Previous studies indicated that the lignin/N ratio was a good predictor of litter decomposition rate (Zhang et al, 2008; Chen et al, 2017). Root litter N was estimated by multiplying root N concentration by the residual root biomass within each litter bag.…”
Section: Methodsmentioning
confidence: 99%